SURVEI TENTANG KONDISI FISIK DAN KEMAMPUAN TEKNIK DASAR PADA SSB SE-KECAMATAN JEPARA KABUPATEN JEPARA (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The problem in this research is how the physical condition and the ability of the basic techniques of soccer at a SSB learners District of Jepara, Jepara ? The purpose of this study was to assess the physical condition and the ability of the basic techniques of soccer as learners SSB District of Jepara Jepara (Kalinga Putra SSB and SSB 18 Jepara). Population is taken as learners SSB District of Jepara, Jepara (Kalinga Putra SSB and SSB 18 Jepara), amounting to 100 people. In this study sampling using a random sample or random sample, ie the majority of the population of learners SSB Kalinga Putra Jepara totaling 50 people, and the majority of the population of learners SSB 18 Jepara, amounting to 50 people. Based on the calculation of descriptive percentage of overall physical condition known to students as the District SSB Jepara Jepara 8% (very well), 17% (good), 50% (medium), 15% (less), and the rest 10% (less than once). To test the ability of the basic techniques of soccer in mind that 71% is included in both categories, and the remaining 29% is included in the medium category.